Diseño de bloque termoaislante con fibra de coco y bagazo de caña para viviendas de interés social - Errazuriz Carrillo, Norma María (2025)
This project aimed to design a thermal insulation block with coconut fiber and sugar cane bagasse for social housing, providing them with greater thermal comfort, since this block was designed to have a low thermal conductivity coefficient by incorporating plant fibers such as sugar cane bagasse and coconut fiber, which are considered agricultural waste. Compression resistance tests were carried out on the blocks with 5 dosages of coconut fiber and sugar cane bagasse, said fibers were subjected to a hydrothermal treatment in order to eliminate their impurities. The first dosage corresponded to the standard block without plant fibers and the fourth dosage had the same percentages as the third dosage, with the difference that it contained sugar cane bagasse treated with sodium hydroxide to improve its adherence to cement and verify its compressive strength. The fourth dosage was the one that obtained the best results in the compression test, with an average of 3,36 MPA....